Relationships between Selected Factors and Adherence to Antiretroviral Therapy among People Living with HIV - Ponboobpha, Aomtip; Maneesriwongul, Wantana; Sa-nongdej, Wanna (Journal of The Royal Thai Army Nurses, 2023)
A descriptive correlation study was conducted to explore relationships between selected factors and antiretroviral therapy adherence among people living with HIV. Selecting a specific sample group according to the inclusion criteria. A sample comprised of 220 people living with HIV who started antiretroviral therapy (ART). Data were collected by using a set of self-administered questionnaires. The content validity of interviewing forms were .96, .94 and .95 respectively and reliabilities were .94, .86 และ .84 respectively Pearson’s product- moment correlation and Spearman’s correlation were used to analyzing data. This study revealed that age, education, and perceived needs for treatment were positively related to antiretroviral therapy adherence among people living with HIV (r = .223, p< .01; r = .164, p< .05; rs = .192, p< .05 respectively). While, the perceived barrier was negatively related to antiretroviral therapy adherence (r = -. 264, p< .05). Other factors were not significantly related to antiretroviral therapy adherence. The findings from this study suggested that nursing interventions enhancing antiretroviral therapy adherence should be provided early to prepare people living with HIV, especially those who are younger age, reported to have low perceived ART needs, and have high perceived barriers to ART.